Theology and poetry in early Byzantium: the Kontakia of Romanos the Melodist - Gador-Whyte, Sarah (Cambridge University Press, 2017)
On the passion of Christ -- The second Adam: a typology of salvation -- The second creation: a new reality for Christians -- The second coming: a theology of time and liturgy -- On the Resurrection IV: conclusions and beyond